Training on evidence-based balneotherapy for medical students: The experience of the University of Parma - Antonelli, Michele; Fasano, Federica; Veronesi, Licia; Donelli, Davide; Vitale, Marco; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2024)
Understanding the scientifically proven properties of balneotherapy is a valuable element in the training of future medical doctors. This article describes the experience, since 2021, at the University of Parma, of teaching the benefits and limits of balneotherapy in the light of the scientific evidence. The Elective Teaching Activity (ETA), titled “Balneotherapy and Health: Scientific Evidence and Future Perspectives”, offers 1 university educational credit to students, and takes place over two consecutive days. The course contents are the following: an overview of the history of thermal baths, specific terminology and classification of water- and mud-based treatments, interpretation of scientific evidence, results of major studies on the topic, regulatory aspects and practical balneotherapy, a virtual tour of a health resort, bibliography, and contacts for further exploration of the subject. In 2023, at the end of the ETA, students were asked to evaluate the course. On average, participants’ knowledge of balneotherapy increased by 42%, while their ability to critically evaluate scientific evidence increased by 20%. All students would recommend the course to their peers. This ETA not only enriches the academic training of medical students but also prepares them to consider balneotherapy as a valid and scientifically supported option in treating various pathologies. (www.actabiomedica.it)